Full-arch prostheses supported by implants with different macrostructures: A multicenter randomized controlled trial - Marcantonio, Ana Carolina Monachini [UNESP]; de Oliveira, Guilherme José Pimentel Lopes; Tassi, Paulo Afonso; Manfrinato, João Paulo Lavagnoli; Segnini, Bruno [UNESP]; de Souza Bezerra Araújo, Raphael Ferreira; Trojan, Larissa Carvalho; Fontão, Flávia Noemy Gasparini Kiatake; de Mattias Sartori, Ivete Aparecida; Sartori, Elisa Mattias; Padovan, Luis Eduardo Marques; Zandim-Barcelos, Daniela Leal [UNESP]; et al. (Wiley, 2025)
Objectives: This study evaluates the clinical performance of implants with hydrophilic surface and two different macrostructures: cylindrical with perforating triangular threads (CT) and cylindrical-tapered with the association of square and condensing and perforating triangular threads (TST). Materials and methods: This was a multicenter split-mouth, simple-blinded, randomized, and controlled trial. Thirty patients with edentulous mandible received two CT and two TST implants. Primary stability was determined by insertion torque and resonance frequency analysis (RFA). Implants were loaded with full fixed-arch prostheses within 24 h after insertion. Clinical parameters (visible plaque index, marginal bleeding index; bleeding on probing; probing depth; and clinical attachment level) and the RFA were assessed at 2, 6, 12, and 24 months after implant loading. Marginal bone level changes were measured by comparison of standardized radiographs taken on the day of implant placement and 6, 12, and 24 months thereafter. Results: Twenty-eight patients completed the 2-year follow-up. The survival rates were 99.16% for CT implants and 100% for TST implants. One CT implant was lost until the 2 months follow-up. No significant differences were found between the two implant types for marginal bone level changes (CT 0.34 [0.24; 0.55 mm]; 0.33 [0.18; 0.55 mm]; 0.41 [0.12; 0.7 mm] vs TST 0.36 [0.14; 0.74 mm]; 0.33 [0.23; 0.63 mm]; 0.30 [0.20; 0.64 mm] at 6, 12, and 24 months, respectively) and other clinical parameters. Conclusion: The macrostructure of the implants had no influence on survival rate, primary and secondary stability, marginal bone level changes, and peri-implant clinical parameters outcomes. Both implants can be predictably used for immediate loading of full-arch mandibular prostheses.
Keywords: implant design; implant-supported rehabilitation; osseointegration; total edentulism